Biophysical insights into the binding capability of Cu(II) schiff base complex with BSA protein and cytotoxicity studies against SiHa - Maity M.; Pramanik U.; Hathwar V.R.; Brandao P.; Mukherjee S.; Maity S.; Maity R.; Maity T.; Chandra Samanta B. (My University, 2025)
Herein, we have explored the effects of chlorinated mononuclear Cu(II) complex upon binding with BSA protein (bovine serum albumin) and its in vitro anti-proliferative potentiality against SiHa cell. The complex was synthesized involving a Schiff base ligand having N,N,O donor centers and characterized by several spectroscopic studies. Structure, DFT studies and Hirshfeld surface (HS) analyses were identified using crystallographic computational studies. The binding interaction with BSA depicts the efficacy of the complex towards promising binding of it with BSA. Further, the complex shows a moderate cytotoxicity against SiHa cancer cell signifying its potentiality as an anti-proliferative agent for human cervix uteri carcinoma. © 2022 The Author(s)